Conversion of fruit waste-derived biomass to highly microporous activated carbon for enhanced CO2 capture. (December 2021) - Serafin, Jarosław; Ouzzine, Mohammed; Cruz, Orlando F.; Sreńscek-Nazzal, Joanna; Campello Gómez, Ignacio; Azar, Fatima-Zahra; Rey Mafull, Carlos A.; Hotza, Dachamir; Rambo, Carlos R.
Highlights: AC'shave been prepared from Amazonian nutshells by chemical activation using KOH. AC's present high volume submicropores (<0.7 nm) up to 91% of total pore volume. The prepared AC's are characterized by a high CO2 capture (4.81 mmol/g) at 298 K. Qisos.h values indicate a strong interaction between pore's surface of AC's and CO2. Abstract: Activated carbons were prepared from different Amazonian fruit waste-derived biomass residues from the Amazon to store CO2 at low pressure. The samples were carbonized in under flowing N2 flow atmosphere and activated with KOH. The carbon materials obtained were physically and structurally characterized by the analysis of N2 isotherms for textural characterization, X-ray fluorescence (XRF), ash content, X-ray diffraction (XRD), Raman spectroscopy, scanning electron microscopy (SEM), and applied for CO2 adsorption. Temperature programmed desorption (TPD), the isosteric heat were also calculated. The values of the specific surface area (SBET ) ranged from 1824 to 2004 m 2 /g, and the total pore volume varied between 0.68 and 0.79 cm 3 /g. These results confirm that the obtained activated carbons are microporous materials. The highest CO2 adsorption under the pressure of 1 bar was achieved in activated carbon derived from andiroba seeds ANKO1, the adsorption of carbon dioxide at 1 bar was being 7.18 and 4.81 mmol/g at 273 K and 298 K, respectively. As a result, the most important factor in the preparation of activated carbon for CO2 capture is primarily rich in extremely the high amount of small micropores.